Immune Status of HIV – Positive Children with Acute Rhinosinusitis - Nuritdin Narzullaev; Suleyman Suleymanov; Adolat Ismailova; Rano Sabitova (Intelektual Pustaka Media Utama, 2013)
The immune status of 25 HIV-positive children with Acute Rhinosinusitis (ARS) has been studied in comparison with the control group of 14 practically healthy children of the same age. HIV-infected patients with ARS have shown deep infringements of the immune status, especially of T-cells and its subpopulations, and impairments of the humoral immunity, suppression of anti-inflammatory cytokine IL-10 and increase of pro-inflammatory IFN-γ. After conducted treatment we have not seen any certain changes of the immune status in HIV positive patients, even in the cases with clinical improvement. It is possible to ascertain only positive changes of IL-10 maintenance and parallel decrease of IFN-γ in the dynamics of treatment.DOI: http://dx.doi.org/10.11591/ijphs.v2i3.2904